Literature Review: Phytochemical Compounds and Pharmacological Activities of Male Carica papaya L. Flower - Andarias, S. Hafidhawatii; Fitriani B.; Yanti, Yoni Rahma; Ferriyanti, Ferriyanti (Jurnal Biologi Tropis, 2025)
Carica papaya L. is a polygamous tropical plant with three sexual forms male, female, and hermaphroditic. Male flowers are reported to contain a variety of phytochemical compounds such as flavonoids, triterpenoids, steroids, alkaloids, and several unique components rarely detected in other plant parts. This article aims to review and analyze existing findings regarding the phytochemical composition and pharmacological activities of male papaya flowers. A literature review approach was used to synthesize scientific information published between 2015 and 2025, systematically retrieved from Scopus, PubMed, and Google Scholar. Data analysis was performed descriptively using chemical compound classification approaches, pharmacological activity clustering, and comparison of findings between studies. The analysis revealed that male papaya flowers are a promising source of bioactive compounds with important antioxidant, anticancer, and antibacterial properties. Variations in the phytochemical profile have been shown to depend on the extraction technique used. Furthermore, studies involving nanoparticle-based formulations have demonstrated increased selectivity against cancer cells and enhanced activity against pathogenic bacteria. However, most current evidence remains limited to in vitro investigations. Therefore, further in vivo and clinical studies are urgently needed to validate its safety, therapeutic efficacy, and potential development as a herbal medicine or phytopharmaceutical agent.